The Holocaust : a history of the Jews of Europe during the Second World War - Gilbert, Martin, 1936-2015. (New York : Holt, Rinehart, and Winston, 1986)
Sets the scene with a brief history of anti-Semitism prior to Hitler, and documents the horrors of the Holocaust from 1933 onward, in an incisive, interpretive account of the genocide of World War II.
First steps to iniquity -- 1933 : the shadow of the swastika -- Towards disinheritance -- After the Nuremberg laws -- "Hunted like rats" -- "The seeds of a terrible vengeance" -- September 1939 : the trapping of Polish Jewry -- "Blood of innocents" -- 1940 : "a wave of evil" -- War in the West : terror in the East -- January-June 1941 : the spreading net -- "It cannot happen!" -- "A crime without a name" -- "Write and record!" -- The "final solution" -- Eye-witness to mass murder -- 20 January 1942 : the Wannsee Conference -- "Journey into the unknown" -- "Another journey into the unknown" -- "If they have enough time, we are lost" -- "Avenge our tormented people" -- From Warsaw to Treblinka : "these disastrous and horrible delays" -- Autumn 1942 : "at a faster pace" -- "The most horrible of all horrors" -- September-November 1942 : the spread of resistance -- "To save at least someone" -- "Help me get more trains" -- Warsaw, April 1943 : hopeless days of revolt -- "The crashing fires of hell" -- "To perish, but with honour" -- "A page of glory ... never to be written" -- "Do not think our spirit is broken" -- "One should like to live a little bit longer" -- From the occupation of Hungary to the Normandy landings -- "May one cry now?" -- July-September 1944 : the last deportations -- September 1944 : the days of awe -- Revolt at Birkenau -- Protectors and persecutors -- The "tainted luck" of survival -- Epilogue: "I will tell the world."
Includes bibliographical references (pages 831-896) and index.
Keywords: 1939-1945; Holocaust, Jewish (1939-1945); Holocauste, 1939-1945.; Holocaust; Joden; True crime literature